Monetización de Datos de Proveedores Marketplace (2021)
Information is a high value asset and with the development of this project seeks to offer a solution that supports the decision making of those suppliers Marketplace and ventures that generate sales through platforms Market. Based on the transactional data provided by a company in the Retail sector, an analysis, consolidation and implementation of a solution was carried out of data, which integrates several technologies, methods and good practices, which in the end provides as a result visualizations presented in Dashboard with different perspectives analysis, which allows the user to make final decisions based on data, to improve your sales and inventory processes and that ultimately results in a better service towards buyers.